Answer:
300
Step-by-step explanation:
Answer:
23
Step-by-step explanation:
The absolute value of any number is just the positive version of that number. For example the absolute value of -12 is 12.
Hope this helps! :)
Answer:
-9
Step-by-step explanation:
Simplify the following:
-6×(-2)/4 (-3)
-6×(-2)/4 (-3) = (-6 (-2) (-3))/4:
(-6 (-2) (-3))/4
The gcd of -2 and 4 is 2, so (-6 (-2) (-3))/4 = (-6 (2 (-1)) (-3))/(2×2) = 2/2×(-6 (-1) (-3))/2 = (-6 (-1) (-3))/2:
(-6-1 (-3))/2
(-6)/2 = (2 (-3))/2 = -3:
--3 (-3)
-3 (-1) = 3:
3 (-3)
3 (-3) = -9:
Answer: -9
angles in a triangle add up to 180
so x = 180 - ( 70 + 90 ) = 20
this is because the two other angles in the both of the identical triangles are 70 and 90